Financiamento federal a estudantes: Proposiç\~oes para remodelagem do Fies, sua integraç\~ao com renúncias e imunidades fiscais e extens\~ao de seu alcance a cursos de EPT - Paulo A. Meyer M. Nascimento; Rafael Rodrigues Tavares; Fabio Bentz Maciel; Abigail Lima dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper discusses pathways to gradually bring about changes in the Student Financing Fund (Fies) with the aim of enabling a broader, more equitable, effective, and efficient student financing model in Brazil. Proposed reforms encompass three dimensions: i) access and enrolment; ii) delinquency; and iii) oversight and remuneration of financial agents. Collectively, the proposed changes would lead to merging Fies with federal scholarship and grant schemes. The revamped program would finance tertiary degrees as well as postsecondary professional certificates, leveraging existing tax exemptions, budgetary resources, and issuance of government bonds. Eligible students would have their tuition fees paid by the government, to be reimbursed if their future incomes allow and in a manner that safeguards their financial health. The federal revenue service would withhold income-contingent repayments to fulfill this propose.
Keywords: I22; 330; Fies; Prouni; Pronatec; student financing; student assistance; income contingent loans